KOMPAS.COM DECONSTRUCTION ON RESHUFFLE STATEMENTS AS A POLITICAL POLICY DURING THE COVID-19 PANDEMIC - Joshua Fernando; Sarwititi Sarwoprasodjo; Dwi Retno Hapsari; Matahari Irandiputri; Ratih Kurnia Hidayati (Bricolage : Jurnal Magister Ilmu Komunikasi, 2021)
The COVID-19 pandemic seems to be a challenge for every country in determining its political-strategic direction. The political policies taken are determining the sustainability of the lives of hundreds of millions of Indonesians. During the COVID-19 pandemic, the reshuffle issue continued to surface and made media coverage very important. Kompas.com is present as a major media that continues to record the development of the reshuffle issue amid the pandemic. This study aims to look at the framing of three reports of kompas.com in different time frames, regarding the reshuffle issue during the COVID-19 pandemic. This study used a qualitative research method with  theory of deconstruction of perspective Jacques Derrida and was sorted using Robert N. Entman's framing analysis. The results of this study found that kompas.com tried to construct public thinking by making opinion articles as an emphasis on news discourse reshuffles which made a shift of people's views to the possibility that resulted in a reshuffle that became a reality.